Assessment of Morphological and Biochemical Characterization of Endophytic Bacteria from Leaves of Tamarind (Tamarindus indica) - Alka Sawarkar; R. K. Sharma; Vidhi Gautam; Madhu Swamy; Anju Nayak; Kabita Roy (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
In the present study, endophytic bacteria were isolated from the leaves of Tamarindus indica and their morphological characterization was done. Endophytes are ubiquitous organisms that live within the host plants without causing any apparent symptom of disease. The aim of the study was to identify the various morphological characteristics of endophytic bacteria from leaves of Tamarindus indica. The preliminary identification of the endophytic bacterial isolates was done based on various morphological features of isolated endophytic bacteria from leaves of Tamarindus indica. Growth characteristics of endophytic bacteria isolated from Tamarindus indica on King’s B media showed that colonies were either irregular or circular in shape, either flat elevation on petri plate or of raised elevation, margin of colonies were either undulated or entire, the surface of the growth opaque and white in colour. All the endophytic bacterial isolates from leaves of Tamarindus indica were non-haemolytic in nature. Growth characteristic of isolated endophytic bacteria from Tamarindus indica in BHI broth showed turbidity and pellicle formation, either they form sediment or ring. The microscopic examination of endophytic bacterial isolates had shown that all endophytic bacterial isolates from Tamarindus indica were gram positive rods. Isolated endophytic bacteria were tested for various biochemical tests also. Based on the findings the endophytic bacteria were characterized and providing insights on the nature of microbiome present in the leaves of Tamarind (Tamarindus indica). Highlights The colony characteristics of endophytic bacteria isolated from leaves of Tamarindus indica were circular in shape with wavy mucoid and soft irregular margin. The colonies were entire, the surface of the growth was smooth, opaque and white in colour.